A Pilot Randomized Crossover Trial of Wet Suction and Conventional Techniques of Endoscopic Ultrasound-Guided Fine-Needle Aspiration for Upper Gastrointestinal Subepithelial Lesions - Mika Takasumi; Takuto Hikichi; Minami Hashimoto; Jun Nakamura; Tsunetaka Kato; Hitomi Kikuchi; Yuichi Waragai; Ko Watanabe; Tadayuki Takagi; Rei Suzuki; Mitsuru Sugimoto; Manabu Hayashi; et al. (Gastroenterology Research and Practice)
Background and Aim. A wet suction technique (“wet” technique) has been developed to improve the quality of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) for sampling various solid lesions. However, no studies have reported on the wet technique for EUS-FNA for gastrointestinal (GI) subepithelial lesions (SELs). We conducted a pilot randomized crossover trial to explore whether the wet technique could be useful with regard to tissue adequacy of upper GI-SELs (UGI-SELs) compared to the conventional EUS-FNA technique (“dry” technique). Methods. Twenty-six patients with UGI-SELs indicated for EUS-FNA were randomly assigned to the dry-first arm using the dry technique for the first two passes or the wet-first arm using the wet technique for the first two passes using a cross-over design with a ratio of 1 : 1. The primary endpoint was the cellularity score of the EUS-FNA specimens rated on a 4-point scale (0-3). The secondary endpoints were the factors influencing cellularity in each suction technique. Results. The mean cellularity score was 1.65±1.20 for the wet technique and 2.00±0.98 for the dry technique (p=0.068). Logistic regression analysis showed that higher cellularity may be related to the final diagnosis of gastrointestinal stromal tumors in the dry technique and the SEL location in the upper stomach in the wet technique. Conclusion. The wet EUS-FNA technique failed to show a potential for improved cellularity of specimens compared to the dry technique for UGI-SELs.